Effects of bark beetle‐caused tree mortality on biogeochemical and biogeophysical MODIS products. Issue 3 (1st July 2013) - Bright, Benjamin C.; Hicke, Jeffrey A.; Meddens, Arjan J. H.
Abstract: [1] Disturbances affect forest‐atmosphere exchanges of carbon, water, and energy, thereby influencing weather and climate. Bark beetle outbreaks are one such disturbance type that alters biogeochemical and biogeophysical processes in forests. Few studies have documented bark beetle impacts to leaf area index (LAI), gross primary productivity (GPP), evapotranspiration (ET), land surface temperature (LST), and surface albedo with satellite observations. Our objective was to use Landsat‐derived estimates of bark beetle‐caused tree mortality and Moderate Resolution Imaging Spectroradiometer (MODIS) land surface products to estimate beetle‐caused changes in LAI, GPP, ET, LST, and surface albedo in northern Colorado. Following bark beetle‐caused tree mortality, decreases occurred in LAI (0.02–0.80 m 2 m −2, 1–40%), annual GPP (50–248 gC m −2  yr −1, (5–26%), and daily summer ET (0.20–0.70 mm day −1, 13–44%), whereas increases occurred in August LST (1–3.9 K) and February albedo (0.03–0.09, 19–52%). We found greater responses of these variables in areas of greater mortality severity. The extent and severity of tree mortality in northern Colorado caused substantial changes in land surface variables (9–23%) when averaged across all forested areas of our study area. Our results demonstrate that land surface variables are sensitive to bark beetle‐caused tree mortality and that bark beetle outbreaks can significantly impact biogeochemical and biogeophysical processes. Key Points: We quantified land surface changes following bark beetle outbreaks with MODIS LST and winter albedo increased following beetle‐caused tree mortality LAI, GPP, and ET (each derived from the same reflectances) decreased